SUCCOR cone study: conization before radical hysterectomy - Chacon, Enrique; Manzour, Nabil; Zanagnolo, Vanna; Querleu, Denis; Núñez-Córdoba, Jorge M; Martin-Calvo, Nerea; Căpîlna, Mihai Emil; Fagotti, Anna; Kucukmetin, Ali; Mom, Constantijne; Chakalova, Galina; Shamistan, Aliyev; et al. (My University, 2022)
To evaluate disease-free survival of cervical conization prior to radical hysterectomy in patients with stage IB1 cervical cancer (International Federation of Gynecology and Obstetrics (FIGO) 2009).